Utilization of iodized salt in the production of salted egg - Isles, Angelica Crisostomo
The Philippine Government legislated RA 8172 an Act Promoting Salt Iodization Nationwide and Related Purposes last December 20, 1996. This Act aims to help alleviate the occurrence of Iodine Deficiency Disease (IDD) in the country. This law requires all local food-grade salt manufacturers to iodized salt. It likewise stipulates that food manufacturers/processors are required to use iodized salt in their operations. In line with our national initiatives to solve that IDD problem in our country, this study determined the effects of using iodized salt on the quality of salted egg. The first phase of the study involved the selection of a commercial process producing the most acceptable salted egg. Among the participating local commercial producers, the process of Gerry de Silva (Producer 3), was the most acceptable. The physico-chemical results of the salted egg samples of Producer 3 were: pH of 7.13, aw of 0.91, and NaCl % of 2.19. The microbiological examination of the samples showed a TPC value of 9.7 x 10^2 cfu/g and YMC value of 7.7 x 10^2 cfu/g. Salted egg sample of Producer 3 was described to be the most acceptable in terms of appearance, texture of yolk, saltiness and overall acceptability. All of these characteristics were evaluated as like moderately. The second phase of the study involved the production of salted egg employing the process of Producer 3. One lot was prepared with iodized salt and another lot for unfortified salt. In the third phase of the study, the salted eggs produced in Phase 2 were subjected to quality assessment. The results of physico-chemical and microbiological tests of salted egg with iodized salt were lower as compared with the control. The pH, aw, and NaCl % of salted egg with iodize salt were 6.60, 0.884, and 2.26%, respectively. In microbiological tests, the TPC and YMC value were of 2.4 x 10^3 cfu/g and 6.0 x 10^2 cfu/g, respectively. NO detectable iodine content was obtained in fresh duck egg and in test samples from every major step of the salted egg process. This can be attributed to the possible reaction of iodine with organic substances present in the clay or perhaps iodine molecule can not penetrate through the egg pores since its atomic size is larger than the pores. If, however, iodine had penetrated into the shell it may form an unexplainable reaction with sulfhydryl groups of albumen (Feeney, 1964). All the obtained results in the physico-chemical and microbiological tests of salted egg with iodized salt were lower as compared to salted egg with unfortified salt. The physico-chemical results of salted eggs with iodized salt were: aw of 0.884, pH of 6.60 and NaCl content of 2.26%. The microbiological results of salted eggs with iodized salt were: TPC value of 3.65 x 10^3 cfu/g and MYC value of 6.0 x 10^2 cfu/g.